2017
DOI: 10.1080/09658211.2017.1393091
|View full text |Cite
|
Sign up to set email alerts
|

How do associative and phonemic overlap interact to boost illusory recollection?

Abstract: This project investigated the underlying mechanisms that boost false remember responses when participants receive study words that are both semantically and phonologically similar to a critical lure. Participants completed a memory task in which they were presented with a list of words all associated with a critical lure. Included within the list of semantic associates was a target that was either semantically associated (e.g., yawn) to the critical lure (e.g., sleep) or shared the initial (e.g., slam) or fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In further tests in English, Hutchison et al (2018) found that adding a single item that shared the initial phonemes with a CI to eight associates in studied lists resulted in a significant boost in false recall and specifically in false remember responses to recalled CIs. This is consistent with models of spoken word recognition that suggest that initial phoneme information is important in narrowing a pool of potential neighbors during word recognition, such as the cohort model (Marslen-Wilson and Tyler, 1980).…”
Section: Manipulations Of Structural Similarity: Phonological and Orthographic Listsmentioning
confidence: 95%
See 1 more Smart Citation
“…In further tests in English, Hutchison et al (2018) found that adding a single item that shared the initial phonemes with a CI to eight associates in studied lists resulted in a significant boost in false recall and specifically in false remember responses to recalled CIs. This is consistent with models of spoken word recognition that suggest that initial phoneme information is important in narrowing a pool of potential neighbors during word recognition, such as the cohort model (Marslen-Wilson and Tyler, 1980).…”
Section: Manipulations Of Structural Similarity: Phonological and Orthographic Listsmentioning
confidence: 95%
“…Research using the DRM paradigm can inform researchers on the interactions between visual word recognition and memory processes, which are often examined separately (e.g., Westbury et al, 2002;Cortese et al, 2008;Hutchison et al, 2018). Specifically, this paradigm can be used to test predictions of word recognition models and results suggest some long-term maintenance or persistence of verbatim information.…”
Section: Manipulations Of Structural Similarity: Phonological and Orthographic Listsmentioning
confidence: 99%
“…Empirical support for the interactive model has been shown in semantically mediated phonological priming, homophone processing [6][7][8] , and false memory studies [9][10][11][12] . In semantically mediated phonological priming studies, it was shown that participants were quicker to respond to targets following primes that were indirectly phonologically related 6,7 .…”
mentioning
confidence: 94%
“…These studies show higher false memories in these hybrid lists compared to pure lists of either kind 10 . Recently, such higher false memories to hybrid lists have been argued to be related to the interactive model 11 . According to this theory, this effect is due to additive activation in both semantic and phonological networks related to the critical lure, allowing this activation to surpass a threshold for output 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that lists comprising semantic and phonological associates result in additive false memories (Finley et al, 2017;Hutchison et al, 2018;McBride et al, 2019;Watson et al, 2003). Watson et al (2003) presented hybrid lists with semantic (e.g., hound, puppy) and phonological associates (e.g., log, dot), related to one critical item (e.g., DOG), in a single list.…”
mentioning
confidence: 99%